Implementation of Javanese Cultural Values Through the Pancasila Student Profile in Merdeka Curriculum - Idana, Rindang Fariha; Insani, Nur Hanifah (STAI Hubbulwathan Duri, 2024)
This study investigates the incorporation of the Pancasila learner profile in the Mardika Basa lan Sastra Jawa textbook for grade VII SMP/MTs and its alignment with Javanese cultural character values. The Pancasila learner profile aims to cultivate students' values and character based on Indonesia's foundational philosophy. Understanding how textbooks reflect these values, particularly within the context of Javanese culture, is important for character education. A descriptive qualitative approach was used to analyze the textbook. Data were collected through data cards, questionnaires, and interviews with teachers. The analysis followed the Miles and Huberman technique, and data validity was ensured through triangulation. The findings indicate that the Mardika Basa lan Sastra Jawa textbook for grade VII, following the Merdeka Curriculum, integrates the Pancasila learner profile in each chapter. This is reflected in the value content, lesson preparation, and learning activities. The Javanese cultural character values corresponding to the Pancasila student profile include andhap asor (humility), babar binuka (openness), tepa salira (tolerance), laku hambeging kartika (noble conduct), wicaksana (wisdom), and niteni, nirokke, nambahi (observe, imitate, add). The study highlights that Javanese cultural values align well with the Pancasila learner profile, contributing positively to character development. These values not only strengthen the national identity but also foster ethical and responsible behavior among students. This research provides valuable insight into how Javanese cultural values can reinforce the Pancasila learner profile in education, supporting national character-building efforts.